Effectiveness of nurse‐led group CBT for hot flushes and night sweats in women with breast cancer: Results of the MENOS4 randomised controlled trial. Issue 10 (24th July 2020) - Fenlon, Deborah; Maishman, Tom; Day, Laura; Nuttall, Jacqueline; May, Carl; Ellis, Mary; Raftery, James; Turner, Lesley; Fields, Jo; Griffiths, Gareth; Hunter, Myra S.
Abstract: Objective: Troublesome hot flushes and night sweats (HFNS) are experienced by many women after treatment for breast cancer, impacting significantly on sleep and quality of life. Cognitive behavioural therapy (CBT) is known to be effective for the alleviation of HFNS. However, it is not known if it can effectively be delivered by specialist nurses. We investigated whether group CBT, delivered by breast care nurses (BCNs), can reduce the impact of HFNS. Methods: We recruited women with primary breast cancer following primary treatment with seven or more HFNS/week (including 4/10 or above on the HFNS problem rating scale), from six UK hospitals to an open, randomised, phase 3 effectiveness trial. Participants were randomised to Group CBT or usual care (UC). The primary endpoint was HFNS problem rating at 26 weeks after randomisation. Secondary outcomes included sleep, depression, anxiety and quality of life. Results: Between 2017 and 2018, 130 participants were recruited (CBT:63, control:67). We found a 46% (6.9‐3.7) reduction in the mean HFNS problem rating score from randomisation to 26 weeks in the CBT arm and a 15% (6.5‐5.5) reduction in the UC arm (adjusted mean difference −1.96, CI −3.68 to −0.23, P = .039). Secondary outcomes, including frequency of HFNS, sleep, anxiety and depression all improved significantly. Conclusion: Our results suggest that specialist nurses can be trained to deliver CBT effectively to alleviate troublesome menopausal hot flushes in women following breast cancer in the NHS setting.